KEADILAN HAM DAN AL-QUR’AN (Tinjauan Atas Penafsiran Ayat-Ayat Hukum) - Muhsin . (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2023)
This article discusses justice from the perspective of human rights and the Qur'an. The main question to be answered in this article is whether human rights and the Qur'an are not contradictory. This is because human rights is a new term that is difficult to find in the holy book, the Qur'an itself. Therefore, human rights and the Qur'an have different standards when making legal decisions. Starting from these different standards, a point of debate arises. Of course, this article examines the points of agreement and debate, so that it can become a healthy discourse, because human rights originate from humans, while the Qur'an is believed by Muslims to be the word of God that cannot contradict human nature. The method used in this article is a comparative method and will present cases of interpretation of legal verses from the perspective of human rights and the Qur'an. The cases taken are universal in nature and related to human justic